2018
DOI: 10.1088/1674-4926/39/2/023001
|View full text |Cite
|
Sign up to set email alerts
|

Composite structure of ZnO films coated with reduced graphene oxide: structural, electrical and electrochemical properties

Abstract: ZnO films coated with reduced graphene oxide (RGO-ZnO) were prepared by a simple chemical approach. The graphene oxide (GO) films transferred onto ZnO films by spin coating were reduced to RGO films by two steps (exposed to hydrazine vapor for 12 h and annealed at 600 °C). The crystal structures, electrical and photoluminescence properties of RGO-ZnO films on quartz substrates were systematically studied. The SEM images illustrated that RGO layers have successfully been coated on the ZnO films very tightly. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…As a consequence, it can be suggested that the conductivity of the ZnO thin film improved by the presence of the rGO into the films structure. A reason for this phenomenon is that graphene shows bipolar nature, so it can transfer electrons and holes almost immediately, which can increase the carrier concentration [46]. The spectra of ZnO and ZnO-rGO_3 thin films are composed of two main peaks.…”
Section: Optical Measurementsmentioning
confidence: 99%
“…As a consequence, it can be suggested that the conductivity of the ZnO thin film improved by the presence of the rGO into the films structure. A reason for this phenomenon is that graphene shows bipolar nature, so it can transfer electrons and holes almost immediately, which can increase the carrier concentration [46]. The spectra of ZnO and ZnO-rGO_3 thin films are composed of two main peaks.…”
Section: Optical Measurementsmentioning
confidence: 99%
“…[34] While, the increase of the lattice parameters in ZnO:Ag/rGO thin film might be due to the residual stress in the sample or to the lattice strain due to the existence of rGO. [35,36] On the other hand, as can be seen in Fig. 3, the sizes decreased remarkably from 24.138 nm to 20 nm after Ag doping, which is due to the restriction caused by the defects in the growth of the crystallites.…”
Section: Xrd Propertiesmentioning
confidence: 86%
“…Sua fase wurtzita não centrossimétrica exibe grandes propriedades piezoelétricas e piroelétricas que o fazer o excelente candidato a aplicações em dispositivos como atuadores mecânicos e sensores piezoelétricos 42,43 . Além disso, é um material tecnológico importante para aplicações em dispositivos eletrônicos e ópticos como células solares, armazenamento de energia, proteção UV, display de emissão de luz (LED), sensores de gás entre outros 39,44 . O ZnO também pode ser sintetizado em diversas nanoestruturas como nanotubos, nanofios, nanorods, nanobelts, tetrápodes e nanofitas 42 .…”
Section: Estrutura E Propriedadesunclassified